Antioxidant Activity and Brine Shrimp Lethality of Punica granatum Fruit Rind - Sundararaju, Dodda; V. Krishnaraju, Alluri; V. Rao, Chirravuri; Trimurtulu, Golakoti (Asian Journal of Chemistry, 2010)
Punica granatum fruit rind extracts were screened for antioxidant activity and brine shrimp lethality assay. All the extracts except hexane extract have shown more potent antioxidant activity compared to BHT, BHA, vitamin C and E. In addition, methanol and aqueous methanol extracts exhibited moderate brine shrimp lethality.